2021
DOI: 10.31234/osf.io/g6qh8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of the impacts of intergenerational engagement on older adults’ cognitive, social, and health outcomes.

Abstract: Background: Promoting older adults’ health and wellbeing via intergenerational engagement can help with the needs of an ageing population. This systematic review evaluated the impacts of intergenerational engagement on cognitive, social, and health outcomes in healthy older adults and older adults with mild cognitive impairment. Research Design and Methods: Comprehensive literature searches were undertaken, with records screened and filtered according to pre-registered criteria. Study quality was formally ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There are currently no other EGMs that exist that address this type of intervention, however, it would complement existing EGMs addressing child welfare. There is a recent scoping review that focuses on outcomes for older people that we will use to inform the framework for our EGM (Krzeczkowska et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…There are currently no other EGMs that exist that address this type of intervention, however, it would complement existing EGMs addressing child welfare. There is a recent scoping review that focuses on outcomes for older people that we will use to inform the framework for our EGM (Krzeczkowska et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We held intergenerational contact events for young to older adults to meet, interact, and build trust and friendship with neighbors of other generations [19]. Previous studies [13,14,17] suggested that sharing recreational activities with different age groups effectively fostered intergenerational relationships. Therefore, the events included recreational activities (e.g., games, handcrafts, stretching, walking) and intergenerational communication.…”
Section: Intergenerational Contact Eventsmentioning
confidence: 99%
“…Intergenerational programs, which promote contact between people from different age groups, may enhance social capital. Such programs typically involve scheduled activities (e.g., reading picture books) that are designed to bring older and younger generations together for the benefit of all participants [13]. Many previous studies reported that intergenerational programs improved older adults' physical and cognitive function [13], reduced ageism [14,15], and enhanced social capital (i.e., social support, norm of reciprocity, and social trust) [13,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care homes are complex environments with an interplay of factors that affect the provision and quality of care provided. While there is evidence to suggest that care homes can create environments in which older adults can receive high-quality care and thrive, there also remains a general sense that more can be done to improve quality of care in the social care sector (Krzeczkowska et al, 2021). Improving the quality of care provided for these individuals is deemed a priority for the UK government.…”
Section: Care Contextmentioning
confidence: 99%